KERJASAMA INDONESIA DAN TIONGKOK DALAM PENGEMBANGAN PARIWISATA DI BALI PERIODE 2013-2017 - Dinda Pertiwi, - (2018)
The tourism sector is one of the most supportive sectors in increasing Indonesia's foreign exchange. Bali is one of the areas in Indonesia which become a main target of destination for domestic people or even international tourist. Based on the Memorandum of Understanding (MoU), the Ministry of Tourism and the state-owned enterprise of Indonesia Tourism Development Corporation (ITDC), it can easily increase the attractiveness in Bali on the grounds that Chinese society has a high percentage rate in tourism, especially in Bali. This series of research is qualitative. Type of research that is descriptive - analysis. Sources of data used are primary and secondary data from interviews, library studies and audio - visual recording of programs run by the Ministry of Tourism and State - Owned Enterprise of Tourism Development Indonesia (ITDC) together with Tiongkok